Is It Possible to Understand the Dynamics of Cryptocurrency Markets Using Econophysics? Crypto-Econophysics - Ulusoy, Tolga; Çelik, Mehmet Yunus (Springer International Publishing, 2019)
Closely related to the entire humanity, Finance, as a scientific field, seeks to meet humanity’s endless needs and to continue its race against time. While doing so, it also benefits from other branches of science. Since speed, reliability, accessibility are at the forefront of model structures, finance continuously improves itself and tries to achieve the best interaction with other disciplines. Financial physics, also known as Econophysics, has brought new statistical methods and insights into the studies. Since thermodynamic laws, one of the most frequently used simulation systems, can explain the basics of all physical movements, the crypto money market, the stock market, and the dynamics of the foreign exchange market have been introduced. Thermodynamics describes heat movements; explain internal energy of economic systems, heat and jobs created (also called wealth or profits), and open a new page in quantitative/qualitative Economic Research. In this study, following the second law of thermodynamics, the Carnot cycle was written with a new point of view from the question of whether the amount of work given to the system in the crypto currency reserve can explain the possible trading (exchange) prices that occur or are likely to occur with the exchange of money.
Keywords: 8. Economic growth; 7. Clean energy